LOCAL CULTURE IN A DISRUPTIVE WORLD - Sandra Dewi Dahlan (Elite : English and Literature Journal, 2023)
This study aimed to describe the implementing digitizing folklore in the English Drama Course to the students of English and Literature Department. In addition, to evaluate the student responses to the project as part of cultural preservation efforts. This study used mixed methods to collect qualitative and quantitative data. The population of the research were fourth semester students of class AG 2/3 of English and Literature Department of UIN Alauddin Makassar. The object was the English Drama Course by applying the "Active Learning" model in the form of digitizing local folklore into animated video. The research technique was carried out by means of observation, interviews and surveys to answer the research questions. The results showed that this project has succeeded in presenting an educational and entertaining animated video for the public watch. In addition, all students involved have responded positively to the implementation of the project and considered the process and implementation were successful and satisfying, especially as an effort to preserve local culture and promote cultural education.